Leon F. Barnard papers - Barnard, Leon F., 1877-1917.; Thomsen, Alice Barnard, 1912-
Transcript of diary and supplement kept by Barnard as secretary of the Baldwin-Ziegler Polar Expedition (1901-1902), as well as photocopies of memoranda, agreements, statements, reports, and newspaper clippings concerning the expedition. Also includes a history of the expedition written by Barnard's daughter, Alice Barnard Thomsen, circa 1993.
Farmer and explorer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Baldwin, Evelyn Briggs, -- 1862-1933.; Ziegler, William, -- 1843-1905.; Polar regions -- Discovery and exploration; Explorers; Farmers